A Study on Parents’ Participation in the Sexuality Education of Their Children in Rural Namibia - Lukolo, Linda Ndeshipandula; Dyk, Agnes van (Challenges in Disease and Health Research Vol. 5, 2021)
This study aims to explore and describe how rural parents are providing sexuality education for their children, to explore and identify the needs of children regarding sexuality education and to identify and describe challenges encountered by rural parents in the provision of sexuality education of their children. Talking about sexuality has never been easy in most Namibians cultures and it seems that most parents feel uncomfortable and embarrassed to talk openly with their children about sexuality. They do not participate in the sexuality education of their children, because they believe they are unable to provide quality and adequate sexuality information due to their lack of knowledge about human sexuality or their perceived inability to explain what they do know. Sexuality education is a lifelong process of acquiring information and forming attitudes, beliefs and values about identity, relationships and intimacy. It encompasses sexuality development, reproductive health, interpersonal relationships, affection, intimacy, body image and gender roles. The ultimate purpose of this study was to develop, describe, implement and evaluate an educational programme to empower rural parents to participate in the sexuality education of their children. The study was designed to be qualitative, explorative, descriptive and contextual in nature. It was performed in three phases. Phase 1 consisted of a situational analysis to explore and describe how parents provide sexuality education. Phase 2 consisted of the development of a conceptual framework that facilitated the development of an educational programme. In phase 3 the programme was implemented and evaluated, recommendations were made and conclusions drawn. The main findings revealed two themes: Factors influencing parental participation in their children’s sexuality education, and the need for parental participation in their children’s sexuality education. This article is part of series of three article stems from a study on the topic of sexuality education empowerment programme of rural parents in Namibia. The three articles have the following titles: one: parent’s participation in sexuality education of their children: A situational analysis; two: conceptual framework developments that facilitate the development of an educational programme and three: programme implementation and evaluation. This article dealt with parent’s participation in sexuality education of their children: a situational analysis. Parents should fulfil an important function as socializing agents by providing norms and values to their children and that they are primary sources from which children obtain their norms and values. Effective sexuality education also provides young people with an opportunity to explore the reasons why people have sex, and to think about how it involves emotions, respect for oneself and other people and their feelings, decisions and bodies.